Comparative Study of Efficacy and Safety Between Monopolar and Bipolar Transurethral Resection of Prostate (TURP) (IAHS Medical Journal, 2025)
Background: Monopolar Transurethral Resection of Prostate (TURP) is the conventional technique for enlarge prostate. In recent years, bipolar TURP has been increasingly being used by the urologist instead of conventional monopolar TURP. This study was aimed to compare the clinical efficacy and safety profile between monopolar TURP and bipolar Transurethral Resection In Saline (TURIS) system for the treatment of symptomatic Benign Enlargement of Prostate (BEP).Materials and methods: This Quasi Experimental Study was conducted in the Department of Urology, Chattogram Medical College Hospital over 110 consecutive patients from 2nd March 2021 to 1st March 2022. Patients were randomly divided in two groups: Monopolar group and bipolar group. Resection time, Bladder irrigation time, six hours postoperative change in Hemoglobin and Serum Sodium and change in International Prostate Symptom Score (IPSS) Quality of life (QoL) and Maximum flow rate (Qmax) after six weeks of surgery were compared in between two groups.Results: Out of 110 enrolled patients, 100 were available in the final follow-up (50 in each group) and included in the final analysis. Both the groups were similar at baseline in terms of their demographic, clinical and laboratory parameters. Duration of prostate resection in bipolar group was longer (68.28±10.62 versus 55.80±6.36 minutes, p